Infiltration of the liver by cells of innate and adaptive immunity and their destruction in development of experimental immune concanavalin-A-induced hepatitis - S. I. Pavlovich; T. M. Bryzgina; N. V. Makogon; L. I. Aleksyuk; T. V. Martynova; R. I. Yanchy; I. N. Alekseyeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study damage of liver tissue, its infiltration by cells of innate and adaptive immunity and cell deathin the development of concanavalin (ConA)-induced hepatitis in mice.Material and methods. Histological, cytologic and biochemical methods were applied. Activity of alanine transaminase in blood serum, activity of myeloperoxidase in liver tissue, cell deathby double vital staining, damage rate of microcirculation channel and parenchyma of the liver, diffuse and focal infiltration and cellular composition of infiltrates were investigated.Results. Primary reaction of the liver at injection ConA consist in inflammatory changes in vascular bed followed by parenchymal disorders. Infiltration by leukocytes in the liver was increased, initially essentially grew neutrophilic, and then - lymphocytic. In the early terms after ConA injection destruction of thymic cells was amplified mainly by apoptotic pathway, and spleen cells – by necrotic pathway.Conclusions. Obtained data assume, that infiltration of the liver by leukocytes, in particular neutrophiles, in combination to ascending necrotic destruction of peripheral cells of innate and adaptive immunity can be the essential pathogenic mechanism at inflammatory liver diseases of T-cell origin.